Acoustic cavitation dynamics of bubble clusters near solid wall: A multiphase lattice Boltzmann approach - Yu Yang; Juan Tu; Minglei Shan; Zijie Zhang; Chen Chen; Haoxiang Li (Ultrasonics Sonochemistry)
Understanding the behavior of cavitation bubble clusters in an acoustic field is crucial for advancing the study of acoustic cavitation. This study uses the multi-relaxation time lattice Boltzmann method (MRT-LBM) to simulate the dynamics of cavitation bubble clusters near a wall, offering new insights into complex cavitation phenomena. The effectiveness of MRT-LBM was verified through thermodynamic consistency, mesh independence, and comparison with the K-M equation solution. The study focuses on the effects of bubble cluster position, acoustic frequency, amplitude, and bubble number on cavitation dynamics. The results found that the impact of bubble cluster proximity to solid boundaries, where smaller offsets result in stronger cavitation effects, significantly increasing wall pressure and jet velocity. The analysis also reveals that low frequencies promote complete bubble collapse, while high frequencies enhance jet velocity but weaken pressure waves. Additionally, higher amplitudes increase jet velocity but disperse energy, reducing wall pressure. Frequency spectrum analysis of wall pressure pw and velocity uw further uncovers significant differences in their spectra and how they influence cavitation intensity, finding that frequency and amplitude are key factors in balancing pressure and jet velocity. These findings underscore the importance of optimizing frequency and amplitude to enhance cavitation effects, which can improve applications relying on acoustic cavitation.